Phenotyping stroke in Sub-Saharan Africa: stroke investigative research and education network (SIREN) phenomics protocol (2015)
Background: As the second leading cause of death and the leading cause of adult-onset disability, stroke is a major public health concern particularly pertinent in Sub-Saharan Africa (SSA), where nearly 80% of all global stroke mortalities occur, and stroke burden is projected to increase in the coming decades. However, traditional and emerging risk factors for stroke in SSA have not been well characterized, thus limiting efforts at curbing its devastating toll. The Stroke Investigative Research and Education Network (SIREN) project is aimed at comprehensively evaluating the key environmental and genomic risk factors for stroke (and its subtypes) in SSA while simultaneously building capacities in phenomics, biobanking, genomics, biostatistics, and bioinformatics for brain research. Methods: SIREN is a transnational, multicentre, hospital and community-based study involving 3,000 cases and 3,000 controls recruited from 8 sites in Ghana and Nigeria. Cases will be hospital-based patients with first stroke within 10 days of onset in whom neurovascular imaging will be performed. Etiological and topographical stroke sub types will be documented for all cases. Controls will be hospital- and community-based participants, matched to cases on the basis of gender, ethnicity, and age (±5 years). Information will be collected on known and proposed emerging risk factors for stroke. Study Significance: SIREN is the largest study of stroke in Africa to date. It is anticipated that it will shed light on the phenotypic characteristics and risk factors of stroke and ultimately provide evidence base for strategic interventions to curtail the burgeoning burden of stroke on the sub-continent.